Integrated perspective on microbe-based production of itaconic acid: from metabolic and strain engineering to upstream and downstream strategies - Nascimento, Miguel Figueiredo (2022)
ABSTRACT: The discovery of itaconic acid as a product of citric acid pyrolytic distillation in 1837 opened the possibility of using it as a polymer building block. Itaconic acid, featuring two carboxylic acids and an unsaturated group, can potentially be used as a building block in several chemical syntheses, with a particular emphasis on polymer manufacture. The elucidation of biochemical pathways originating from itaconic acid, first in Aspergillus terreus and, recently, in several species of the Ustilago genus, has intensified and diversified research focused on microbe-based itaconic acid production, including at an industrial scale. These efforts include the engineering of naturally producing species/strains along with the exploration of other species that do not naturally produce itaconic acid but may offer potential benefits. The use of renewable wastes or sugar-enriched residues as substrates to produce itaconic acid, from a circular bioeconomy perspective, is another important aspect of the advancements in microbial itaconic acid production. This review provides an overview of the achievements as well as the challenges concerning the engineering of the producing strains/species, substrate selection, optimisation of bioreactor operation, and downstream itaconic acid purification methods.